Copper Cladding CPW Fed Single Layer Antenna for UWB Applications - S. , Suganthi; P. , Thiruvalar Selvan (International Journal of Psychosocial Rehabilitation, 2020)
A CPW-fed has been designed for multiband application, which includes ultra-wide and Ku band. The antenna was etched on a single-layer copper-cladding substrate, of which the material was FR4 with relative permittivity of 4.4, and the magnitude was 40.0 mm × 50.0 mm × 1.6 mm. The parameters of the antenna are simulated and optimized with HFSS. This paper proposes a new CPW-fed UWB antenna that operates at the bandwidth that covers the 2.4–6.2 GHz range for UWB band and 10.2 to 15.1 for Ku band applications with return loss ≤ -10 dB. The relative bandwidth of 110% has been achieved in addition to good radiation patterns and gain. Simulated and measured results for return loss, radiation pattern, and gain were presented. A good agreement has been obtained between the simulation and experiment, and the proposed antenna meets the requirements of the ultra-wideband antenna.